A 9-aminoacridine derivative induces growth inhibition of Ehrlich ascites carcinoma cells and antinociceptive effect in mice - Mangueira, Vivianne M.; de Sousa, Tatyanna K. G.; Batista, Tatianne M.; de Abrantes, Renata A.; Moura, Ana Paula G.; Ferreira, Rafael C.; de Almeida, Reinaldo N.; Braga, Renan M.; Leite, Fagner Carvalho; Medeiros, Karina C. de P.; Cavalcanti, Misael Azevedo T.; Moura, Ricardo O.; et al. (Frontiers in Pharmacology, 2022)
Acridine derivatives have been found with anticancer and antinociceptive activities. Herein, we aimed to evaluate the toxicological, antitumor, and antinociceptive actions of N’-(6-chloro-2-methoxyacridin-9-yl)-2-cyanoacetohydrazide (ACS-AZ), a 9-aminoacridine derivative with antimalarial activity. The toxicity was assessed by acute toxicity and micronucleus tests in mice. The in vivo antitumor effect of ACS-AZ (12.5, 25, or 50 mg/kg, intraperitoneally, i.p.) was determined using the Ehrlich tumor model, and toxicity. The antinociceptive efficacy of the compound (50 mg/kg, i.p.) was investigated using formalin and hot plate assays in mice. The role of the opioid system was also investigated. In the acute toxicity test, the LD50 (lethal dose 50%) value was 500 mg/kg (i.p.), and no detectable genotoxic effect was observed. After a 7-day treatment, ACS-AZ significantly (p < 0.05) reduced tumor cell viability and peritumoral microvessels density, suggesting antiangiogenic action. In addition, ACS-AZ reduced (p < 0.05) IL-1β and CCL-2 levels, which may be related to the antiangiogenic effect, while increasing (p < 0.05) TNF-α and IL-4 levels, which are related to its direct cytotoxicity. ACS-AZ also decreased (p < 0.05) oxidative stress and nitric oxide (NO) levels, both of which are crucial mediators in cancer known for their angiogenic action. Moreover, weak toxicological effects were recorded after a 7-day treatment (biochemical, hematological, and histological parameters). Concerning antinociceptive activity, ACS-AZ was effective on hotplate and formalin (early and late phases) tests (p < 0.05), characteristic of analgesic agents with central action. Through pretreatment with the non-selective (naloxone) and μ1-selective (naloxonazine) opioid antagonists, we observed that the antinociceptive effect of ACS-AZ is mediated mainly by μ1-opioid receptors (p < 0.05). In conclusion, ACS-AZ has low toxicity and antitumoral activity related to cytotoxic and antiangiogenic actions that involve the modulation of reactive oxygen species, NO, and cytokine levels, in addition to antinociceptive properties involving the opioid system.